Transpiração em Árvores Isoladas de um Montado de Azinho: Evolução Sazonal e Condicionantes Hidráulicas - David, Teresa Soares; Ferreira, Isabel; Pereira, João Santos; Cohen, Shabtai; David, Jorge Soares (Silva Lusitana, 2002)
Sapflow and related variables were monitored for two years in an isolated Quercus rotundifolia Lam. tree, in a low density oak woodland (montado) near Évora. The study aimed at identifying tree strategies in adverse soil and climatic conditions in order to understand the conditions for survival and sustainability. Seasonal variations in transpiration, mainly related to solar radiation and vapour pressure deficit, showed a peak in summer (3 mm day-1) even in dry soil conditions. Water availability to the roots did not change much over time, due to the likely access of the root system to an aquifer located at 13 m depth. Stomatal control prevents transpiration from exceeding the maximum water uptake capacity by the roots. An upper limit is thus imposed on transpiration, preventing leaf water potential to decrease below -3,2 MPa, which may probably be the threshold for cavitation
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: aquifer; Evapotranspiration; Quercus rotundifolia Lam.; sapflow

Transpiração em Árvores Isoladas de um Montado de Azinho: Evolução Sazonal e Condicionantes Hidráulicas - David, Teresa Soares; Ferreira, Isabel; Pereira, João Santos; Cohen, Shabtai; David, Jorge Soares (Silva Lusitana, 2002)
Sapflow and related variables were monitored for two years in an isolated Quercus rotundifolia Lam. tree, in a low density oak woodland (montado) near Évora. The study aimed at identifying tree strategies in adverse soil and climatic conditions in order to understand the conditions for survival and sustainability. Seasonal variations in transpiration, mainly related to solar radiation and vapour pressure deficit, showed a peak in summer (3 mm day-1) even in dry soil conditions. Water availability to the roots did not change much over time, due to the likely access of the root system to an aquifer located at 13 m depth. Stomatal control prevents transpiration from exceeding the maximum water uptake capacity by the roots. An upper limit is thus imposed on transpiration, preventing leaf water potential to decrease below -3,2 MPa, which may probably be the threshold for cavitation
Keywords: aquifer; Evapotranspiration; Quercus rotundifolia Lam.; sapflow